2018
DOI: 10.1016/j.ijrobp.2018.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Based Outcomes for 24 Gy in 2 Daily Fractions for Patients with de Novo Spinal Metastases Treated With Spine Stereotactic Body Radiation Therapy (SBRT)

Abstract: Twenty-four Gray in 2 daily fractions is safe and effective in achieving high tumor control rates for de novo spinal metastases. These outcomes will serve as a benchmark for the ongoing Symptom Control-24 randomized trial comparing 24 Gy in 2 SBRT fractions to 20 Gy delivered in 5 daily conventional fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 25 publications
4
66
0
Order By: Relevance
“…15 Cunha et al and Thibault et al 10,28 also found that doses per fraction of ≥20Gy were associated with higher VCF rates in their analyses. These data are consistent with the 39% rate of VCF with high-dose single-fraction SBRT by Rose et al and the modest 8.5% rate of VCF with 24Gy in 2 fractions by Tseng et al 19,25 The benefit of high-dose singlefraction radiotherapy is higher rates of local control, especially with tumours considered radio-resistant such as renal cell carcinoma. 34,35 However, there has not been a published randomised trial assessing the efficacy and adverse effect profile of varying SBRT fractionations for spine metastases.…”
Section: Relationship Between Sbrt and Vcfsupporting
confidence: 86%
See 4 more Smart Citations
“…15 Cunha et al and Thibault et al 10,28 also found that doses per fraction of ≥20Gy were associated with higher VCF rates in their analyses. These data are consistent with the 39% rate of VCF with high-dose single-fraction SBRT by Rose et al and the modest 8.5% rate of VCF with 24Gy in 2 fractions by Tseng et al 19,25 The benefit of high-dose singlefraction radiotherapy is higher rates of local control, especially with tumours considered radio-resistant such as renal cell carcinoma. 34,35 However, there has not been a published randomised trial assessing the efficacy and adverse effect profile of varying SBRT fractionations for spine metastases.…”
Section: Relationship Between Sbrt and Vcfsupporting
confidence: 86%
“…The 15 studies identified are listed in Table 2 with the relevant findings. 10,19,20,[22][23][24][25][26][27][28][29][30][31][32][33] The majority involved patients with diverse primary tumour locations or histologies. Thibault et al focused specifically on patients with renal cell carcinoma (RCC) metastases, and Yoo et al only reported lesions from hepatocellular carcinoma (HCC) origin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations